Observational Study on the Variability of Mixed Layer Depth in the Bering Sea and the Chukchi Sea in the Summer of 2019 - Jiao, Xiaohui; Zhang, Jicai; Li, Qun; Li, Chunyan (Frontiers in Marine Science, 2022)
Based on the CTD data from 58 stations in the Bering Sea and the Chukchi Sea in the summer of 2019, the values of mixed layer depth (MLD) were obtained by using the density difference threshold method. It was concluded that the MLD can be estimated more accurately by using a criterion of 0.125 kg/m^3 in this region. The average MLD in the Bering Sea basin was larger than that in the Bering Sea shelf, and both of them were smaller than that in the Bering Sea slope. The MLD increased northward in both the Chukchi Sea shelf and the Chukchi Sea slope. The farther northward, the greater the difference between the MLD calculated from temperature (MLDt) and the MLD calculated from density (MLDd). The water masses and their interaction played an important role in the variation of MLD in the northern Bering Sea shelf and Chukchi Sea. The MLD was large due to the vertically homogeneous Anadyr Water in the northwestern Bering Sea shelf. The horizontal advection of Bering Sea Anadyr Water and Alaska Coastal Water in the Bering Sea shelf led to shallower MLD in the central northern Bering Sea shelf. The westward advection of the Alaska Coastal Water caused shallow mixed layers (ML) in some regions of the Chukchi Sea shelf in the summer of 2019. The observed large MLD at BL01 station near the Aleutian Island was caused by an anticyclonic eddy. The northward increase in the MLD in the Chukchi Sea was related to the low-salinity seawater from sea ice melting in summer. The spatial variation of MLD was also closely related to the surface momentum flux and the sea surface buoyancy flux. Stratification plays an even more important role in determining the variation of MLD. The ML in 2019 was shallower and warmer than those in previous years, especially in the Bering Sea shelf and Chukchi Sea where sea ice volume, thickness, and coverage were significantly larger than the Bering Sea basin, which was related to the small sea ice volume in winter and spring of 2019 compared to previous years.